Creole - portraits of France's foreign relations during the long nineteenth century - Grigsby, Darcy Grimaldo 19XX- (The Pennsylvania State University Press, 2022)
"Examines visual representations of and by persons defined as Creole, the term applied to white, Black, and mixed-race persons born in French colonies during the nineteenth century"--
Includes bibliographical references and index
Keywords: Geschichte 1800-1900; Kolonialismus; Schwarze -- Motiv; Bildnismalerei; Frankreich; Portraits, French / 19th century; Racially mixed people in art; Creoles / France / Colonies